INTERBUDGETARY RELATIONS IN THE SYSTEM OF BUDGET REGULATION (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. The article is devoted to the study of the essence of interbudgetary relations in the system of budgetary regulation, key aspects of their regulation, instruments of interbudgetary relations and their application in Ukraine under martial law.The purpose of the article. The purpose and objective of the article is to study the essence and relevance of the problem of formation of interbudgetary relations under martial law.Results. The author analyzes the approaches and defines various aspects of the essence of intergovernmental fiscal relations based on the literature. The characteristics of different approaches to the interpretation of the essence of the concept of ‘intergovernmental fiscal relations’ are presented.The mechanism of horizontal equalization of the tax capacity of the territory is outlined according to the Budget Code of Ukraine. The mechanism of transferring intergovernmental transfers from the state budget to local budgets and intergovernmental transfers between local budgets is determined.The author considers the types of subsidies and subventions provided from the State budget to local budgets. Their amounts are analyzed.It is proved that the system of horizontal financial equalization redistributes financial resources in favor of those local authorities which have an imbalance and provides partial compensation for the losses of local budgets of territorial communities from the lack of personal income tax.Conclusions. It is concluded that the financial basis for the development of any state is budgetary funds. Interbudgetary relations are the main instrument for ensuring the proper functioning of the national budget system.
Keywords: local budgets, mechanism, budget, budget system, interbudgetary relations, intergovernmental transfers, financial resources, subventions, subsidies.